2017
DOI: 10.1080/07347332.2017.1312661
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to medical help-seeking among older men with prostate cancer

Abstract: The barriers identified in our study strengthen the evidence for the impact of traditional masculinity on help-seeking in men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 47 publications
1
36
1
Order By: Relevance
“…In contrast to evidence reviews in relation to initial health seeking behaviours of men this study did not find gender differences to disclosure; the men reported being just as likely to disclose symptoms of genital oedema to female HCP as to male HCP. This may be because the patient participants were further on in their treatment pathway and had already accommodated to discussion of genital issues with female health professionals.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to evidence reviews in relation to initial health seeking behaviours of men this study did not find gender differences to disclosure; the men reported being just as likely to disclose symptoms of genital oedema to female HCP as to male HCP. This may be because the patient participants were further on in their treatment pathway and had already accommodated to discussion of genital issues with female health professionals.…”
Section: Discussioncontrasting
confidence: 99%
“…However, a limiting factor would be that some men, particularly older men, have been found to be reluctant to discuss and disclose problems of a genital nature, affecting their initial health-seeking behaviours. 22,23 Whilst a pilot study by Sampuro et al 21 found that men with prostate cancer were able to disclose more sensitive information in written than verbal form, this study indicated that using a tool which had patient generated images and vocabulary, the LGUCQ, enabled earlier and more accurate disclosure and helped normalize the experience.…”
Section: Discussionmentioning
confidence: 93%
“…This was in agreement with study conducted by Michelleking et al (2017) which revealed that, men belief that urinary tract symptoms are associated with ageing and that sexual changes are secretive and a taboo. Further this was in consistency with study done on barriers to medical help-seeking practices among older men with prostate cancer which showed that negative attitude towards help seeking behaviors was related to male gender role, fear of the health condition, medical and treatment procedures and embarrassment as a consequence of medical examinations and communication with health and non-health professionals to include disclosure of sexual-related symptoms (Perucha et al (2017). Social cultural factors that influenced health seeking practices among men suffering from LUTS attending surgical outpatient clinic included employment, where by formal employment (p=0.001), being a casual (0.003) and also being a farmer (p=0.002) had statistical significant influence on health seeking practices.…”
Section: Discussionsupporting
confidence: 81%
“…Researchers ( 13 - 14 ) state that the body’s disease process undermines the maintenance of hegemonic masculinity, as it presents dilemmas in identity, including subordination, passivity, recognition of emotions, and dependence. Specifically in cancer, men reconfigure their physical and social identity and seek to preserve their family masculinity status as much as possible, but liminality is an inevitable process, as biological imbalance reflects directly on social actions by altering male identity.…”
Section: Discussionmentioning
confidence: 99%